Labrador, aerial view of Torngat Mountains - Forbes, Alexander, 1882-1965 (1931)
(Series 18) Inland flight from the Button Islands to Eclipse Harbor. Camera facing right front to line of flight. Fig. 82 - Looking southwest across the northern range of the Torngat Mountains. The mountains in the foreground of Figure 81 appear in the distance to the left as the conspicuous flat-topped summit. Aug. 3, 1931. Forbes, A., Miller, O. M., Odell, N. E., & Abbe, E. C. (1938). Northernmost Labrador mapped from the air. New York: American Geographical Society. Grayscale